Optimal Taxation and Economic Growth in Tunisia: Short and Long Run Analysis - Chokri, Terzi; Anis, El Ammari; Ali, Bouchrika (Journal of Reviews on Global Economics, 2018)
Tax policy is among the most common and relevant instruments in the toolkit of policy-makers when thinking about promoting growth, yet there is not compelling evidence regarding its effect in Tunisia. Using a variety of approaches, we measure firstly the optimal tax burden rate using Scully's static model and the quadratic model. For Scully's static model, gross domestic product is the dependent variable. For the quadratic model, growth rate is a dependent variable explained by tax rate in level and in square. Secondly and according to stationary and cointegration test results, we focus on the long-term effects on gross domestic product of the important taxes, namely tax revenue and private receipts. In this second study, we use a basic Scully model and we develop a vector error correction model technique. Our results show that optimal tax burden rate has to be situated between 12.8% and 19.6% of gross domestic product which is widely lower than the current rates. The long-term analysis estimates an optimal rate of 14% of gross domestic product which can participate to increase economic growth, to stabilize the tax evasion and to encourage investment especially after the Tunisian revolution.